Simple and sensitive high performance liquid chromatography method with fluorescence detection for therapeutic drug monitoring of topiramate - Milosheska, Daniela (Acta chimica slovenica, 2015)
Objective of the present report was to develop and validate a simple, sensitive, reliable, inexpensive and reproducible HPLC method with fluorescence detection (HPLC-FLD), suitable for routine therapeutic drug monitoring (TDM) of an antiepileptic drug topiramate. The determination of plasma topiramate concentration was carried out after precolumn derivatization, using 4-chloro-7-nitrobenzofurazan as a fluorescent labeling agent and bendroflumethiazide as an internal standard. The standard calibration curve was linear over the concentration range of 0.01-24 microg/mL (r2> 0.9998). The intra- and inter-day accuracies expressed as bias were from 1.41 to 9.95 % and from 1.85 to 10.23 %, respectively. The intra- and inter-day precisions were below 7.87 % and 2.73 %, respectively. A simple, sensitive, accurate, precise and inexpensive HPLC-FLD method for determination of topiramate in human plasma was developed and validated. The validated method was applied for the measurement of plasma topiramate concentrations in patients with epilepsy. The reported method is appropriate for TDM of topiramate as well as for pharmacokinetic and bioequivalence studies.
Keywords: človeška plazma; tekočinska kromatografija visoke ločljivosti s fluorescenčno detekcijo; terapevtsko nadziranje zdravila; topiramat